2020
DOI: 10.1186/s12877-020-1459-6
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of older adults, caregivers, and healthcare providers on frailty screening: a qualitative study

Abstract: Background Screening is an important component of understanding and managing frailty. This study examined older adults’, caregivers’ and healthcare providers’ perspectives on frailty and frailty screening. Methods Fourteen older adults and caregivers and 14 healthcare providers completed individual or focus group interviews. Interviews were audio recorded, transcribed verbatim, and analyzed using line-by-line emergent coding techniques and inductive thematic analysis. Results The interviews yielded several t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 44 publications
4
25
0
Order By: Relevance
“…Stakeholders' level of understanding on frailty seen in our study was in line with results from previous studies in Canada (17,29), especially from the perspective of aging as well as physical, cognitive and social factors. Similar to our ndings, these two studies, conducted on participants from health clinics, found that healthcare providers possessed various levels of understanding regarding frailty, and recognized aging and physical factors to be the most important aspects of frailty.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
See 3 more Smart Citations
“…Stakeholders' level of understanding on frailty seen in our study was in line with results from previous studies in Canada (17,29), especially from the perspective of aging as well as physical, cognitive and social factors. Similar to our ndings, these two studies, conducted on participants from health clinics, found that healthcare providers possessed various levels of understanding regarding frailty, and recognized aging and physical factors to be the most important aspects of frailty.…”
Section: Comparison With Existing Literaturesupporting
confidence: 91%
“…The need to better de ne frailty and the use of a standardized tool to ensure consistent and transferable results as suggested by the participants was also shown by several studies (29,33). A study in the Netherlands (29) found that the lack of guidelines for care after frailty screening prevented frailty screening programs from being implemented. In the A&E setting speci cally, due to patients' reduced function and increased vulnerability, it would be challenging to obtain accurate frailty screening results (29).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, participants described the importance of a holistic approach to unravel the older patient as a whole beyond just the medical complaints. The need of older people to receive holistic care and to be involved in decision-making has been described previously for the ED setting [ 25 ], and is corresponding to literature in community-dwelling older people and older patients in regular health care [ 26 29 ]. Our findings suggest that screening could aid in reaching this goal and additionally could help to comfort patients by means of attention for them as a person.…”
Section: Discussionmentioning
confidence: 99%